Art, Architecture, and the Moving Viewer, c. 300-1500 CE
1 online resource.
Keywords: Premodern architecture and built environments were fluid spaces whose configurations and meanings were constantly adapting and changing. The production of transitory meaning transpired whenever a body or object moved through these dynamic spaces. Whether spanning the short duration of a procession or the centuries of a building's longue durée , a body or object in motion created in-the-moment narratives that unfolded through time and space. The authors in this volume forge new approaches to architectural studies by focusing on the interaction between monuments, artworks, and their viewers at different points in space and time. Contributors are Christopher A. Born, Elizabeth Carson Pastan, Nicole Corrigan, Gillian B. Elliott, Barbara Franzé, Anne Heath, Philip Jacks, Divya Kumar-Dumas, Brigitte Kurmann-Schwarz, Ashley J. Laverock, Susan Leibacher Ward, Elodie Leschot, Meghan Mattsson McGinnis, Michael Sizer, Kelly Thor, and Laura J. Whatley.